Goodbye, things : on minimalist living - Sasaki, Fumio, 1979- (Penguin Books, 2017)
SELF-HELP & PERSONAL DEVELOPMENT. 'Throw it away now. It'll be your start of everything...' Fumio Sasaki is not an enlightened minimalism expert. He's just a regular guy who was stressed at work, insecure, and constantly comparing himself to others - until one day he decided to throw away everything he didn't feel like he truly needed, including books, clothes, musical instruments, furniture and gadgets. While this process wasn't easy, the benefits were instantaneous and absolutely remarkable: without all his stuff, Sasaki finally felt true freedom, peace of mind, and a new kind of happiness. Goodbye, Things explores why we measure our worth by the things we own and how minimalism will not only transform our space but truly enrich our lives. Along the way, Sasaki modestly shares his personal minimalist experience, offering tips on the minimizing process and revealing the profound ways in which he has changed since he got rid of everything he didn't truly need